Urgensi Pendidikan bagi Perempuan dalam Menghadapi Generasi Alpha Perspektif Tematik Tafsir Al-Azhar - Mulyani, Eka; Burhanudin Yusuf, Enjang (Indo-MathEdu Intellectuals Journal, 2023)
Women are the key to the quality of a nation. Women's education is a very basic need so that women could give birth to a critical attitude towards things that happen in the development of each generation. Generation Alpha is the birth of a baby who already understands technological developments and is presented with various conveniences. The purpose of this research is so that as a woman, she knows how important education is and what the limitations are in networking with technological developments. This research uses the Tahlili exegesis method, namely by examining the verses of the Al-Quran from various points of view and carrying out analysis based on the opinions of various figures to explain the main points of discussion, so that it is easy to achieve what is desired. The data collection method is by explaining the meaning of each word in the Al-Qur'an, explaining each verse with other verses explained in the al-Azhar tafsir, analyzing the interpreter's explanation of the tafsir verse from the laws of fiqh that can be applied in everyday life. Tafsir Al-Azhar provides many explanations regarding the verses of the Koran that include women, how the Koran places women as something special. Apart from that, the expression that women are the first madrasah for the family, is a characteristic of how women have become quite important for the nation's generations. This is a focus for educators, how we protect our nature as women